Integrated Morphological and Phytochemical Analysis of Mesua ferrea L. and Calophyllum inophyllum L.: Implications for Authenticity in Herbal Practices - Liviya Gaikwad; Aparna Saraf (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This study evaluates the suitability of Calophyllum inophyllum L. buds as a substitute for Mesua ferrea L. stamens (Nagkesar), a valued botanical in Indian traditional medicine. Economic pressures and regional availability often lead to unverified substitutions, raising concerns about therapeutic consistency. To address this, both samples were subjected to comprehensive analyses using Field Emission Gun Scanning Electron Microscopy (FEGSEM), Fourier Transform Infrared Spectroscopy (FTIR), Gas Chromatography–Mass Spectrometry (GC–MS), High-Performance Liquid Chromatography (HPLC), and High-Resolution LC–MS Orbitrap. FEGSEM revealed distinct epidermal features in Calophyllum inophyllum L. buds, lacking the pollen morphology seen in Mesua ferrea L. FTIR analyses demonstrated notable differences in functional groups, with Mesua ferrea L. showing stronger signatures of flavonoid-associated hydroxyl groups. GC–MS profiling highlighted divergent chemical classes: Mesua ferrea L. was rich in oxygenated sesquiterpenes, while Calophyllum inophyllum L. contained long-chain alkanes, esters, and aromatic hydrocarbons. HPLC and LC–MS Orbitrap confirmed the presence of Mesuaferrone A—a biflavonoid uniquely found in Mesua ferrea L. —absent in Calophyllum inophyllum. One-way ANOVA of LC–MS retention times across Alkaloids, Acids, and Flavonoids revealed a statistically significant difference, further supporting the chemical non-equivalence of the two species. These findings confirm that Calophyllum inophyllum L. is not a suitable phytochemical substitute for Mesua ferrea L. stamens. The study advocates for rigorous authentication and regulatory measures in traditional medicine to ensure product efficacy and consumer safety.